2018
DOI: 10.1111/aos.13998
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine profiles of phakic and pseudophakic eyes with primary retinal detachment

Abstract: Purpose To compare the cytokine profiles of phakic (p) and pseudophakic (ps) eyes with primary rhegmatogenous retinal detachment ( RD ) to eyes with macular holes ( MH ) and to identify differences in the specific cytokine profiles. Methods Aqueous humour ( AH ) and vitreous fluid ( VF ) were obtained from patients with primary RD withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 46 publications
2
18
0
Order By: Relevance
“…Vitreous fluid contains many kinds of cytokines and growth factors, such as tumor necrosis factor-α, interleukin-6, interleukin-8, basic fibroblast growth factor (bFGF), VEGF, platelet-derived growth factor (PDGF), and hepatocyte growth factor (HGF) [36,37]. The levels of these factors are elevated in vitreous fluid in patients with retinal detachment and are thought to contribute to the onset of PVR [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Vitreous fluid contains many kinds of cytokines and growth factors, such as tumor necrosis factor-α, interleukin-6, interleukin-8, basic fibroblast growth factor (bFGF), VEGF, platelet-derived growth factor (PDGF), and hepatocyte growth factor (HGF) [36,37]. The levels of these factors are elevated in vitreous fluid in patients with retinal detachment and are thought to contribute to the onset of PVR [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…[78][79][80][81][82][83] IL-6 can also stimulate corneal epithelial cells and stromal fibroblasts (and macrophages) to produce profibrotic VEGF. 78 Like most inflammatory cytokines, IL-6 is present in subretinal fluid in high titers during retinal detachment and RRD repair, 84,85 and their presence is correlated with the subsequent, development of postoperative PVR, 9 as well as being elevated in the vitreous of patients with early PVR, 38,86 and correlating with PVR severity when found in sub silicone-oil fluid, 87 but, because subretinal and vitreous IL-6 levels significantly overlap between patients with uncomplicated retinal detachment and severe or future PVR, they have limited biomarker potential.…”
Section: Interleukin-6mentioning
confidence: 99%
“…[31] Garweg et al documented that the levels of 39 of 43 cytokines in the vitreous and 23 of 43 cytokines in the aqueous humour were significantly higher in eyes with RRD than in those with MH and they could not find relevant differences in the cytokine profiles of phakic and pseudophakic eyes. [32] Zandi et al evaluated the same 43 cytokines in RRD, moderate, and advanced PVR compared to MH. They revealed that eyes with PVR C2-D showed higher levels of CCL27 (CTACK), CXCL12 (SDF-1), CXCL10 (IP-10), CXCL9 (MIG), CXCL6, IL-4, IL-16, CCL8 (MCP-2), CCL22, CCL15 (MIP-1delta), CCL19 (MIP-3beta), CCL23 and compared to controls.…”
Section: Plos Onementioning
confidence: 99%